The VISTA Carina Nebula Survey - I. Introduction and source catalog - Preibisch, Thomas; Zeidler, Peter (Astronomy and astrophysics, 2014)
Context: The Carina Nebula is one of the most massive and active star-forming regions in our Galaxy and has been studied with numerous multiwavelength observations in the past five years. However, most of these studies were restricted to the inner parts (≲1 square-degree) of the nebula, and thus covered only a small fraction of the whole cloud complex. Aims: Our aim was to conduct a near-infrared survey that covers the full spatial extent (~5 square-degrees) of the Carina Nebula complex and is sensitive enough to detect all associated young stars through extinctions of up to AV ≈ 6 mag. Methods: We used the 4m Visible and Infrared Survey Telescope for Astronomy (VISTA) of ESO to map an area of 6.7 square-degrees around the Carina Nebula in the near-infrared J-, H-, Ks-bands. Results: The analysis of our VISTA data revealed 4 840 807 individual near-infrared sources, 3 951 580 of which are detected in at least two bands. The faintest SN ≥ 3 detections have magnitudes of J ≈ 21.2, H ≈ 19.9, and Ks ≈ 19.3. For objects at the distance of the Carina Nebula (2.3 kpc), our catalog is estimated to be complete down to stellar masses of ≈0.1 M⊙ for young stars with extinctions of AV ≈ 5 mag; for regions in the brightest parts of the central nebula with particularly strong diffuse emission, the completeness limit is at slightly higher stellar masses. We describe the photometric calibration, the characteristics, and the quality of these data. VISTA images of several newly detected or yet rarely studied clusters in the outer parts of the Carina Nebula complex are presented. Finally, a list of stars with high proper motions that were discovered in our analysis is provided in an appendix. Conclusions: Our catalog represents by far the most comprehensive deep near-infrared catalog of the Carina Nebula complex. It provides a new basis for spatially complete investigations of the young stellar population in this important star-forming complex.
Gesehen am 04.11.2020